2020
DOI: 10.1186/s12955-020-01294-3
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Chinese version of the Amsterdam Preoperative Anxiety and Information Scale (APAIS)

Abstract: Background: Preoperative anxiety is an unpleasant state of tension that may impact patients' post-operative pain and satisfaction. The level of preoperative anxiety should be routinely identified. The Amsterdam Preoperative Anxiety and Information Scale (APAIS) is a self-reported questionnaire that is used to quickly assess preoperative anxiety and information needs with good psychometric properties. Objectives: To validate the Chinese version of the Amsterdam Preoperative Anxiety and Information Scale (APAIS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 23 publications
0
31
0
Order By: Relevance
“…All items are rated on a scale from 1 (not at all) to 5 (extremely). The APAIS has been translated into various languages -Chinese (Wu et al, 2020), Czech (Zeleníková et al, 2017), French (Maurice-Szamburski et al, 2013, German (Berth et al, 2007), Italian (Buonanno et al, 2017), Japanese (Nishimori et al, 2002), Malay (Mohd Fahmi et al, 2015), Spanish (Vergara-Romero et al, 2017), Turkish (Çetinkaya et al, 2019) and others. The Surgical Fear Questionnaire (SFQ) was published in 2014 (Theunissen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…All items are rated on a scale from 1 (not at all) to 5 (extremely). The APAIS has been translated into various languages -Chinese (Wu et al, 2020), Czech (Zeleníková et al, 2017), French (Maurice-Szamburski et al, 2013, German (Berth et al, 2007), Italian (Buonanno et al, 2017), Japanese (Nishimori et al, 2002), Malay (Mohd Fahmi et al, 2015), Spanish (Vergara-Romero et al, 2017), Turkish (Çetinkaya et al, 2019) and others. The Surgical Fear Questionnaire (SFQ) was published in 2014 (Theunissen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For example, this might be attributable to some cultural aspects regarding anxiety and fear in the Serbian population and ways of coping with those feelings. This is supported by the fact that the Serbian version is not only different from the original, but it also differs from the Malay (Mohd et al., 2015), Chinese (Wu et al., 2020), French (Maurice‐Szamburski et al., 2013), Japanese (Nishimori et al., 2002), and Italian (Buonanno et al., 2017) version as well. To the best of our knowledge, Greek validation study is the only study that showed an identical two‐factor structure of the translated and validated APAIS, with clearly separated anesthesia and procedure‐related subscales (Bakalaki et al., 2017).…”
Section: Discussionmentioning
confidence: 96%
“…The Amsterdam Preoperative Anxiety and Information Scale (APAIS) was developed in 1996 by Moerman et al. (1996) and the original Dutch version has been translated and validated into many reliable versions in several languages (Maurice‐Szamburski et al., 2013; Mohd et al., 2015; Vergara‐Romero et al., 2017; Wu et al., 2020). Nowadays, APAIS has gained widespread use, since contemporary literature offers strong evidence of its validity and reliability (Aust et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the HADS, APAIS places more attention on anesthesia and the examination itself, which can better reflect the subjective feelings of patients [ 14 ]. The Chinese version of APAIS has been proved as an effective tool for assessing patients’ preoperative anxiety [ 8 ]. There is no research focusing on the change of LUTS caused by cystoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…The order of bladder examination remained consistent between the two groups. The day before the cystoscopy, patients were informed about the type of cystoscope, and then filled out the Amsterdam Preoperative Anxiety and Information Scale (APAIS), which has been proved as a reliable method for assessing preoperative anxiety [ 8 ]. Patients were asked to select the pain level and score immediately according to the visual analogue scale (VAS) after the cystoscopy.…”
Section: Methodsmentioning
confidence: 99%